Humoral immune responses to Theileria parva in cattle as measured by two-dimensional Western blotting - Kishima, M.; Dolan, T.T.; Njamunggeh, R.E.G.; Nkonge, C.G.; Spooner, P.R. (Springer, 1995)
Humoral immune responses to schizont antigens from six stocks of Theileria parva were compared by two-dimensional Western blotting using sera from cattle that had been infected with a T. parva stock or a clone. Isoelectric points of a polymorphic immunodominant molecule (PIM) of schizonts that induces strong antibody responses in cattle ranged from acidic to basic. Molecular masses (Mr) of the PIM of the respective T. parva stocks were as follows: T. parva Muguga. 86 kDa; Mariakani. 83 kDa; Marikebuni. 83 kDa; Uganda, 83 kDa; T. parva Boleni, 83 kDa; and T. parva 7014, 100 kDa. Among nine cattle infected with T. parva Muguga, four produced antibodies to a basic antigen having an Mr of 32 kDa. The PIM of T. parva Muguga, T. parva Boleni, and T. parva 7014 reacted strongly with serum obtained from an animal that had been infected with T. parva Muguga. Two-dimensional Western blotting using antischizont monoclonal antibodies enabled us to differentiate between stocks of T. parva.